Limited self-control, obesity and the loss of happiness - Alois Stutzer (Institute for the Study of Labor (IZA), 2007)
Obesity has become a major health issue. Research in economics has provided important insights as to how technological progress reduced the relative price of food and contributed to the increase in obesity. However, the increased availability of food might well have overstrained will power and led to suboptimal consumption decisions relative to people's own standards. We propose the economics of happiness as an approach to study the phenomenon. Based on proxy measures for experienced utility, it is possible to directly address whether certain observed behavior is suboptimal and therefore reduces a person's well-being. It is found that obesity decreases the well-being of individuals who report limited self-control, but not otherwise.
Keywords: 360; Gesundheitsrisiko; Nahrungsmittelkonsum; Persönlichkeitspsychologie; Lebenszufriedenheit; Schweiz